Expenditure Incidence Analysis: A Gender-Responsive Budgeting Tool for Educational Expenditure in Timor-Leste? - Austen, Siobhan; Costa, M.; Sharp, R.; Elson, D. (Routledge, 2013)
Gender-disaggregated expenditure incidence analysis (EIA) is a tool for assessing the gender responsiveness of budgets and policies. However, to date there has been a limited take-up of gender-disaggregated EIA in policy and budget decision making. Using data from the 2007 Timor-Leste Living Standards Survey (TLLSS) and interviews and discussions with stakeholders, this paper conducts an EIA of expenditures on public schools and discusses the effectiveness of this analysis as an input into budget decision making. While gender-disaggregated EIA can assist in identifying gender gaps, its potential can only be fulfilled when combined with additional gender analysis and supported by a deepunderstanding of budget decision-making processes and the actors involved. The gender-disaggregated EIA of Timor- Leste’s educational spending confirmed its usefulness as an indicator of inequalities in educational expenditure. However, a range of political, cultural, and technical barriers constrains the use of gender-disaggregated EIA in policy and budget decision making.